Добова динаміка водного режиму листків Betula pendula Roth та їхня адаптивна реакція - Rositska, N.V.; Zaimenko, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The results of investigation water regime influence on accumulation the content of lipid peroxidation product and free proline in Betula pendula Roth leaves were shown. The direct relationship between the lipid peroxidation product content and water degree in the Betula pendula leaves was established. The significant increasing of lipid peroxidation product content and free proline in leaves during the day has been shown adaptive potential growth in plants.